SIDOARJO REGENCY MSME EXIT STRATEGY IN TERMS OF PERSONALITY TRAITS, ENTREPRENEUR SKILLS, AND DIGITAL MARKETING - Handoko Eko Prasstyo; Wisnu Panggah Setiyono (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Personality Traits, Entrepreneurial Skills, and Digital Marketing on the Exit Strategy of Micro, Small, and Medium Enterprises (MSMEs) in Sidoarjo Regency. Method: A quantitative approach was employed, involving a population of food and beverage MSMEs in Sidoarjo Regency. The sample consisted of 50 respondents selected using a simple random sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis to determine the relationship and significance between the studied variables. Results: The findings indicate that entrepreneurial skills and digital marketing have a significant positive effect on MSME exit strategies, while personality traits show a weaker but still relevant influence. These results highlight the importance of strategic skill development and digital adaptation for MSME sustainability and planned business transition. Novelty: This study provides new insights into how psychological and digital factors jointly shape MSME exit strategies in regional contexts, emphasizing the growing role of digital competence as a determinant of successful business exits in the modern entrepreneurial landscape.